Waste Assessment Model (WAM): Bagaimana Perusahaan Menilai Limbah? Indonesia - Irawan, Yeremias Budi; Fitriani, Katlea (Jurnal Sains dan Teknologi Lingkungan, 2024)
The results of the initial analysis carried out by the author occurred because there were several indications of waste problems at PT XYZ. These problems are the difference in actual time and standard time as well as the quality of production results that do not meet company standards. The purpose of this research is to determine the type of relationship between waste and the type of waste produced in the production process at PT Best Jeans Indo Citra Nusa. This research applies a mixed method research method, combining quantitative and qualitative data through observation, interviews, and literature study. The study population includes all PT XYZ employees, with a sample of 8 people selected using judgment sampling. The analysis was carried out using the Waste Assessment Method, which aims to identify and evaluate waste in the production process. This method consists of the Waste Relationship Matrix and the Waste Assessment Questionnaire. The occurrence of idle time and defects in the production process at PT XYZ can occur because the company still produces waste in every production process. With this research, it is hoped that companies can make efforts to minimize every process that can produce waste.